(untitled) (Academic journal Industrial Machine Building Civil Engineering, 2017)
One of the important issues of environmental security is the possibility of natural or man-caused accidents on the objects of increased responsibility, which include buildings and constructions of nuclear power plants (NPP). It is an extremely important task, to guarantee a safe work of nuclear power plants, as well as a safety of staff and environment. According to the regulated international and industry standards, the construction of buildings and nuclear power plants are to be relied on seismic effects is required in order to establish the boundary seismic resistance, and also finding the kinematic parameters of the building. The calculation of buildings and structures on the seismic effects should be carried out taking into account the interaction between the foundation and ground base. The problem of interaction between the foundation and soil base occupies a central place in the general theory of seismic stability.